Another Antimagic Decomposition of Generalized Peterzen Graph - Nur Inayah; M. Irvan Septiar Musti; Soffi Nur Masyithoh (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2021)
AbstractA decomposition of a graph P into a family Q consisting of isomorphic copies of a graph Q is (a,b)-Q-antimagic if there is a bijection φ:V(P)∪E(P)→1,2,3,4…,v_P+e_P such that for all subgraphs Q’ isomorphic to Q, the Q-weightsφ(Q’ )=∑_(v∈V(Q^' ))▒φ(v) + ∑_(e∈E(Q^'))▒〖φ(e)〗constitute an arithmetic progression a,a + b,a + 2b,…,a + (r - 1)b where a and b are positive integers and r is the number of subgraphs of P isomorphic to Q. In this article, we prove the existence of a (a,b)-P_4-antimagic decomposition of a generalized Peterzen graph GPz(n,3) for several values of b.Keywords: covering; decomposition; antimagic; generalized Peterzen. AbstrakSuatu dekomposisi dari suatu graf P ke dalam suatu famili Q yang terdiri dari salinan isomorfik dari graf Q dikatakan (a,b)-Q-antiajaib jika terdapat pemetaaan bijektif φ:V(P)∪E(P)→1,2,3,4…,v_P+e_P sedemikian sehingga semua subgraf Q’ yang isomorfik ke Q, dengan bobot-Q sebagai berikutφ(Q’ )=∑_(v∈V(Q^' ))▒φ(v) + ∑_(e∈E(Q^'))▒〖φ(e)〗yang membentuk suatu barisan aritmatika yaitu a,a + b,a + 2b,…,a + (r - 1)b dengan a dan b adalah bilangan bulat positif dan r adalah banyaknya subgraf dari P yang isomorfik ke Q. Pada artikel ini, kami membuktikan eksistensi (a,b)-P_4-antiajaib dekomposisi dari graf generalized Peterzen GPz(n,3) untuk beberapa nilai b.Kata kunci: selimut; dekomposisi; antiajaib; generalized Peterzen.